35-[63:(23-280:80:20)+40-18:9×11]=
Răspunsuri la întrebare
Răspuns de
0
35 - [63 : (23 - 280 : 80 : 20) + 40 - 18 : 9 * 11] =
35 - [63 : (23 - 0,175) + 40 - 22] =
35 - [63 : 22,825 + 18] =
35 - [2,76 + 18] =
35 - 20,76 =
14,24
35 - [63 : (23 - 0,175) + 40 - 22] =
35 - [63 : 22,825 + 18] =
35 - [2,76 + 18] =
35 - 20,76 =
14,24
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă